1009 Clinical Uncertainty and the Paediatric Trainee. (October 2012) - Deasy, AM; Elbadry, M; Loftus, A; Nicholson, AJ; O'Neill, MB
Abstract : Background and Aims: Uncertainty is at the heart of clinical practice and is encountered by trainees at all levels. This study explored paediatrics trainees' perceptions of uncertainty. Methods: Basic specialist trainees in Paediatrics were surveyed while attending a training day. The survey explored 4 aspects related to uncertainty which included factors in decision making, personal impact of uncertainty, the response to colleague's clinical error and strategies to address uncertainty. Data obtained included gender and year of graduation. A likert scoring system was used (cuing at 1, not at all and at 6, definitely), to rate responses. A don′t know option was also allowed. Results: Forty two (100%) trainees responded. The M:F was 1:2.9. The mean Likert scores for factors impacting on clinical decisions were 5.7 for clinical knowledge and experience, 5.4 for opinion of senior colleagues, 4.6 for fear of making a mistake, 4.2 for parent anxieties and expectations .Twenty one (50%) of trainees frequently reflect on cases when at home .Their confident decisions are modified by opinions of senior colleague mean likert score 4. Mean Likert scores for responses to error scenario by a colleague were sympathy 4.3, acceptance 4.4, and anxiety 3. Mean Likert scores for strategies to address uncertainty included enhanced teaching 5.9, enhanced clinical experience 5.8, knowledge of 'red flags' 5.7, mentoring 5.6, building resilience 4.9, and developing self awareness 4.5. Conclusion: Paediatric trainees are impacted by clinical uncertainty which transfers into their home life. Incorporating strategies in training to enhance coping skills is necessary.